Pola Komunikasi Pemimpin Terhadap Tingkat Kepatuhan Anak Didik - Putra, Heri Rahmatsyah; Aini Safitri; Fadhlur Rahman Armi (Idarah (Jurnal Pendidikan dan Kependidikan), 2021)
A harmless organization will not be able to run as it should. Human relationships are created through good communication patterns, as well as things in organizations. Lead communication with members will influence members' attitude and motivation to advance the organization. This study is aimed at finding out the communication patterns of the leader in increasing the level of dancer engagement at the training center of Sri Kemuning Bagansiapiapi. The method used in this study is a quantitative method descriptive with data analysis through simple statistical data calculation and explains the research results data. Data collection techniques using observation guides, interviews, commissioner guides and documentation studies. Research shows that the major contribution of the communication pattern to the participants' association was 83.33% or 25 participants said that the communication pattern affects the participants' association in the arts training centre, The category is very high, while 5 participants are raised or 16.66% say that the communication pattern affects the association of participants with a high category suggesting that the leader is able to properly organize all the potential of the participants raised. Leaders at Sri Kemuning Art Training Center use to give examples to trainers and educated participants with good communication patterns that can enhance discipline, in communicating, so that a comfort, unity and learning for educated participants to undergo existing procedures.